2020
DOI: 10.1039/c9nr10084a
|View full text |Cite
|
Sign up to set email alerts
|

General synthesis of Pd–pm (pm = Ga, In, Sn, Pb, Bi) alloy nanosheet assemblies for advanced electrocatalysis

Abstract: A universal synthesis approach has been proposed to produce a series of well-defined Pd–pm (pm = Ga, In, Sn, Pb, Bi) alloy nanosheet assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…Thus, PdRh, PdIr, PdMo, PdGa, and PdBi nanosheets have been successfully synthesized, all of which show excellent electrocatalytic performance for electrochemical reactions. [28][29][30]…”
Section: Co-confined Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, PdRh, PdIr, PdMo, PdGa, and PdBi nanosheets have been successfully synthesized, all of which show excellent electrocatalytic performance for electrochemical reactions. [28][29][30]…”
Section: Co-confined Synthesismentioning
confidence: 99%
“…In terms of the classification from chemical composition, metallic nanomaterials can be classified into precious metal‐based and nonprecious metal‐based catalysts. Generally, precious metal catalysts include Pt‐group elements (Pt, Pd, Os, Ru, Rh, and Ir), [ 28 ] while nonprevious metal catalysts mainly consist of other 3d transition metal element, such as Fe, Co, Ni, Cu, Zn, and Ag. [ 29 ] Introducing two or more elements into Pt‐group elements could yield precious metal‐based nanomaterials, while the other metallic nanomaterials could be defined as nonprecious metal‐based metallic catalysts.…”
Section: Brief Classification Of Ldmnsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modulated electronic structure is necessary for a high‐active catalyst because it is favourable for lowing the adsorption energy of the reactants adsorbed on the catalyst surface. For metal electrocatalysts, one of the most effective strategies to modify their electronic structure is to introduce the second or more metal elements into Pt matrix to form bimetallic or multi‐metallic nanocrystals [46,99–103] . The d‐band centre of Pt will be shifted because the mismatch arrangement of atoms in Pt‐based bimetallic or multi‐metallic catalysts results in lattice strain, including tensile strain and compressive stress.…”
Section: Advanced Strategies For High‐performance Aor Electrocatalystsmentioning
confidence: 99%
“…In addition, doping one more element into nanocrystals is also a well‐known approach to boost catalytic activity and durability [42,43] . In comparison with commonly used transition metals, Ga, a p‐block metal, was sporadically reported to have positive impact on activity and durability of platinum‐group metals electrocatalysts [43,44] . For example, Huang and his co‐workers have demonstrated that doping Ga in Pt nanowires can significantly improve the catalytic activity and durability for ORR by the strong p‐d hybridization interactions [32] .…”
Section: Introductionmentioning
confidence: 99%